Quality of Recovery After General Anesthesia with Remimazolam in Patients’ Undergoing Urologic Surgery: A Randomized Controlled Trial Comparing Remimazolam with Propofol - Mao Y; Guo J; Yuan J; Zhao E; Yang J (Drug Design, Development and Therapy, 2022)
Yuanyuan Mao, Jin Guo, Jingjing Yuan, Erxian Zhao, Jianjun Yang Department of Anesthesiology, Pain and Perioperative Medicine, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People’s Republic of ChinaCorrespondence: Jianjun Yang, Department of Anesthesiology, Pain and Perioperative Medicine, The First Affiliated Hospital of Zhengzhou University, No.1 East Jianshe Road, Zhengzhou, Henan, 450052, People’s Republic of China, Tel/Fax +8613783537619, Email Jianjunyang1971@163.comBackground: Remimazolam is a new medication with sedative and hypnotic effects. It has been demonstrated non-inferior to propofol in general anesthesia with regard to efficacy and safety. However, whether general anesthesia with remimazolam is better than propofol in terms of patients’ recovery quality remains unknown.Patients and Methods: Patients enrolled in this study were randomized to remimazolam or propofol group. In remimazolam group, general anesthesia was induced with remimazolam and sufentanil and maintained with remimazolam and remifentanil. In propofol group, general anesthesia was induced with propofol and sufentanil and maintained with propofol and remifentanil. Neuromuscular blocking agent cisatracurium was also injected during anesthesia. Sedation level was monitored by bispectral index (BIS). Our primary outcome was the quality of patients’ postoperative recovery, using the Quality of Recovery-15 (QoR-15) scale. Secondary outcomes included SpO2, HR, MBP and frequency of application of vasoactive drugs during anesthesia, as well as incidences of adverse events in the post anesthesia care unit (PACU).Results: The global scores of QoR-15 scale were lower in remimazolam group at postoperative day 1 and day 3 compared to propofol group, but differences between the two groups only had clinical significance at postoperative day 1. Among the five dimensions of QoR-15 scale, scores for physical comfort and emotional state were lower in remimazolam group than propofol group. MBP and HR were higher in remimazolam group than propofol group after anesthesia induction. SpO2 was similar in the two groups. The frequency of application of vasoactive drugs during anesthesia was higher in propofol group than remimazolam group. There was no statistical difference in the incidences of adverse events between the two groups.Conclusion: General anesthesia with remimazolam can provide more stable hemodynamics but also cause temporary reduction in the quality of recovery in patients undergoing urologic surgery, compared to propofol.Keywords: remimazolam, propofol, quality of recovery, urologic surgery